Three-dimensional modeling of inland waters optical properties from aerial hyperspectral images - Carmo, Alisson Fernando Coelho do [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The acquisition of data using Remote Sensing and in-situ sampling allows several data sources to be integrated for the analysis and observations of environmental characteristics and may require computational methods to support the data processing, exploration and analysis. The need to integrate data from different sources is highlighted in studies of dynamic and complex environments that frequently change, such as hydroelectric reservoirs. Reservoirs are artificial ecosystems, which influence directly the regional characteristics, mainly because of their multipurpose use. The interactions of the electromagnetic energy with the optically active components occur along the entire water column, so that the behavior of the light field reflects the changes applied along the entire euphotic zone. However, the values taken from images are used accordingly to a plane and associated with the respective point or area of surface. The calibration of bio-optical models considering only the surface sampling data can not deliver fully effective results because the electromagnetic radiation interacts with the components located along the water column and the response captured by the sensors does not only represent the value associated with the surface. Considering this scenario, this work proposes an investigation on the influence of the vertical distribution of the optical properties along the water column, in order to contemplate records about the interaction in different levels of depth, besides the spatial disposition itself, being configured as a genuinely three-dimensional environment. For that, data collected by in situ spectral sensors and by hyperspectral camera in an aerial platform are used to construct the model. Finally, it is expected that the final product of this investigation, composed of the three-dimensional model adjusted from semi-analytical and empirical relations, may be an unprecedented contribution to the Remote Sensing area, and allow to identify relations along the water body volume which may assist as subsidies for the improvement of bio-optical models and derivation from other related studies about depth-related optical properties.

A aquisição de dados por meio da combinação de Sensoriamento Remoto e amostragens in-situ permite que várias fontes de dados sejam integradas para a análise e observação de características do alvo de interesse e pode exigir métodos computacionais para apoiar o processamento, exploração e análise de dados. A necessidade de integrar dados de diferentes fontes é destacada em estudos de ambientes dinâmicos e complexos que se alteram frequentemente, como os reservatórios hidrelétricos. Os reservatórios são ecossistemas artificiais, que influenciam diretamente nas características regionais, principalmente devido ao seu uso múltiplo uso. As interações da energia eletromagnética com os componentes opticamente ativos ocorrem ao longo de toda a coluna d’água, de modo que o comportamento do campo de luz reflete as mudanças aplicadas ao longo da zona eufótica. No entanto, as grandezas registradas nas imagens são usados de acordo com o plano e limitadas ao respectivo ponto ou área da superfície. A calibração de modelos bio-ópticos, considerando apenas os dados de amostragem da superfície, pode não fornecer resultados totalmente eficazes, porque a radiação eletromagnética interage com os componentes localizados ao longo da coluna de água e, consequentemente, a resposta capturada pelos sensores não representa apenas o valor associado à superfície. Este trabalho propõe uma investigação sobre a influência da distribuição vertical das propriedades ópticas ao longo da coluna d’água, a fim de contemplar registros sobre a interação em diferentes níveis de profundidade, além da própria disposição espacial, configurando-se como um ambiente genuinamente tridimensional. Para isso, dados coletados por sensores espectrais in-situ e por câmera hiperespectral embarcada em uma plataforma aérea foram usados para construir o modelo. Por fim, espera-se que o produto final desta investigação, composto pelo modelo tridimensional ajustado a partir de relações semi-analíticas e empíricas, possa ser uma contribuição inédita para a área de Sensoriamento Remoto e permitir identificar relações ao longo do volume de água que pode fornecer subsídios para a melhoria de modelos bio-ópticos e derivação de outros estudos relacionados à propriedades ópticas em diferentes profundidades.
Modelagem tridimensional de propriedades ópticas em águas interiores utilizando imagens hiperspectrais
Keywords: Three-dimensional bio-optical model; Optical Properties; Vertical distribution of light; Inland Water; Modelo bio-óptico tridimensional; Propriedades ópticas; Distribuição vertical da luz; Águas Interiores